Perianal abscess: a descriptive analysis of cases treated at the Hospital Santa Marcelina, São Paulo - Neto,Isaac José Felippe Corrêa (2016)
Abstract Introduction Perianal suppurations have an incidence of 1–2:10,000 inhabitants per year and represent about 5% of proctology consultations, more frequently in males, being rare in childhood. Although perianal or anorectal abscess is an entity of relatively simple diagnosis and treatment, in a considerable percentage of patients difficulties will be found, especially considering that the initial treatment of these patients is performed by non-specialist physicians. Objective This is a retrospective survey of cases of perianal and anorectal abscess operated in Santa Marcelina Hospital between October 2011 and December 2014. Patients and methods A retrospective study of patients operated on an emergency basis for perianal and/or anorectal abscess in Santa Marcelina Hospital between October 2011 and December 2014, being excluded patients with inflammatory bowel disease. Data of gender, age, clinical presentation, the season of the year in which the abscess occurred, time of progression of symptoms, comorbidities, signs of Systemic Inflammatory Response Syndrome (SIRS) on admission, surgeries carried out, reoperations and clinical outcome were analyzed. Results Electronic medical records of 52 patients (73.1% male) who underwent surgical treatment of anorectal and perianal abscess were analyzed. The mean overall age was 43.03 years, and all patients reported pain as the main symptom, with a mean time of symptoms of 6.5 days. As for the season of the year of onset and diagnosis of perianal abscess, 61.5% of patients had this pathology in the summer and spring months. Conclusion In our study, it can be observed a higher incidence of perianal abscess in males and in the warmer months; furthermore, just over half of the patients developed perianal fistula in their progression.